The last séance : tales of the supernatural [compact disc, unabridged] - Christie, Agatha, 1890-1976 (Harper Audio, 2019)
"For lovers of the supernatural and the macabre comes this collection of ghostly and chilling stories from legendary mystery writer Agatha Christie. Fantastic psychic visions, specters looming in the shadows, encounters with deities, a man who switches bodies with a cat--be sure to keep the light on whilst reading these tales."--Amazon.com